(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This research explores the educational potential of reading literacy lessons in fostering patriotism among primary school students. The study particularly emphasizes the use of innovative methods in teaching literary texts to develop national consciousness and devotion to the homeland. Methods such as observation, experimental testing, interviews, and content analysis were applied to demonstrate the effectiveness of innovative approaches through practical examples.